Champion : the graphic novel - Dragoon, Leigh, 1976- (G.P. Putnam's Sons, 2017)
In a futuristic San Francisco, June and Day have moved on after their work to save the Republic. June works as Princeps-Elect for the Republic, and Day has a high-level military position. Then, just as a peace treaty is about to be signed, a deadly plague breaks out in the colonies causing panic, and the border cities fear war. June is the only one who knows how to defend her country, but saving thousands of lives will mean asking Day to give up everything.